Analysis of Prediabetes Risk Factors at Primary Health Care Centers - Russy Novita Andriani; Yogi Fitriadi; Cornelia Wahyu Danawati; Hari Koesnanto; Robikhul Ikhsan (Faculty of Medicine, Public Health, and Nursing, 2022)
Background: The condition of prediabetes is still reversible whereas diabetes is irreversible. Prediabetes prevalence continues to increase rapidly worldwide. It is estimated that >470 million people will have prediabetes by 2030. The prevalence and risk factors for the cause of prediabetes in the Daerah Istimewa Yogyakarta (DIY) are not known because there was not enough research and data. Yogyakarta has a high risk of prediabetes because Yogyakarta has the highest level of sugar consumption in Indonesia (16.9%). Objective: This research aimed to analyze the risk factors for prediabetes and identify the most dominant risk factors for prediabetes in primary health care centers at DIY. Methods: This observational, analytical research used a cross-sectional study approach. The population of this research was the population in DIY. The subjects of the research were a group of individuals aged >25 years in Sleman and Bantul who met the inclusion and exclusion criteria. A sample size estimate of the study was a minimum of 312 patients. The data were analyzed by using chi square and multivariate logistic regression with significance set as p<0.05. Results: The research was conducted in two districts of Sleman and Bantul. The total number of study subjects was 346 and 67people were excluded because they had diabetes. Subjects with hypertension and prediabetes were 20 people and statistically significant with the value of p = 0.001 (Prevalence Ratio (PR) = 3.16 95% CI: 2.85-3.46). Age was also associated with the incidence of prediabetes with p = 0.029. The results of the multivariate logistic regression analysis were p>0.05 was hypertension (p = 0.022, PR 4.239; 95% CI: 0.203-0.962) and central obesity (p = 0.040, PR 5.253; 95% CI: 0.163-0.868). Conclusion: Prediabetes prevalence was 11.1% in the study population. The risk factors associated with the incidence of prediabetes were age, central obesity and hypertension. The most dominant factor was central obesity.